Изучение содержания химических элементов в лесных напочвенных мхах и подстилающих почвах; Известия вузов. Физика; Т. 54, № 11 (2) - Рогова Н. С. Наталья Сергеевна; Рыжакова Н. К. Надежда Кирилловна; Меркулов В. Г. Виктор Георгиевич; Борисенко А. Л. Алексей Леонидович (2011, 2011)
Заглавие с экрана